Caring-Based Supportive Educative Enhance Prevention Ability Of Diabetic Ulcers In Patients With Type II Diabetes - Elyk Dwi Mumpuningtias; Emdat Suprayitno; Cory Nelia Damayanti (Poltekkes Kemenkes Surakarta, 2022)
Background: Patients with diabetes mellitus are at risk for complications of diabetic foot ulcers. This complication can avoid if people with diabetes mellitus have the proper knowledge of self-care management. This study aimed to determine the effect of self-care management education on preventing foot ulcers in patients with type II diabetes mellitus. Methods: The design of this study is quasi-experiment. The number of samples was 86 with a simple randomized sample divided into two groups, 43 in the treatment group caring base supportive educative activities, and 43 in the control group distributing leaflets on diabetes. Results from studies were analyzed using the paired t-test and the independent t- test. Results: These study results are based on independent t-test scores of self-care management in the treatment and control groups after the intervention, namely p = 0.002. The difference in the delta score of self-care management scores in the treatment and control groups after the intervention was p=0.000. Conclusion: The results showed that self-care management education interventions effectively increased the ability of self-care patients with type II diabetes mellitus to prevent complications of diabetic ulcers. This intervention can be a promotive effort to increase self-care independence in patients with type II diabetes mellitus to avoid complications of diabetic wounds.